The Connections Between the Soft Commodity Futures Market and Food Price Stability - Marek SZTURO (Communications of International Proceedings, 2021)
In recent years, soft commodities have been subject to increasing speculative price fluctuations driven by the futures markets. The aim of the article was to assess the relationship between soft commodity futures market and soft commodity prices. The increase in volatility of benchmarks and the development of markets for transactions based on them suggests their impact on the price situation in soft commodities markets. The phenomenon of increased volatility of soft commodity prices, partly not caused by natural factors, may have negative consequences for the markets of production factors, including renewable and non-renewable resources.
Keywords: Futures Markets; Soft Commodities; Food Prices.